A Case of Tenofovir-associated Fanconi Syndrome in Patient with Chronic Hepatitis B - Kim, Dongwoo; Lee, Jongjin; Kim, Dae-ha; Kang, Kyuho; Suh, Sang Jun; Jung, Young Kul; Yim, Hyung Joon (The Korean journal of gastroenterology, 2016)
Tenofovir disoproxil fumarate (TDF) is one of the most widely used treatment options for human immunodeficiency virus (HIV) and HBV infections. Despite its efficacy and safety, some cases of nephrotoxicity have been reported in the treatment of HIV patients. Even more recently, very few cases of Fanconi syndrome associated with tenofovir therapy in HBV monoinfection have been reported. Herein, we report a case of a 47-year-old male with an HBV monoinfection, who developed Fanconi syndrome and a secondary osteomalacia with multiple bone pain. After TDF withdrawal and supplementation of calcitriol, his renal function was reverted. Although the overall risk of TDF-associated nephrotoxicity is very low, both glomerular and tubular function should be monitored in patients undergoing TDF treatment.